PENGARUH KESADARAN MASYARAKAT TERHADAP EFEKTIVITAS PENGELOLAAN SAMPAH DI DESA TIMORENG PANUA KECAMATAN PANCA RIJANG KABUPATEN SIDENRENG RAPPANG - Melsy Andini Putri; Abdul Jabbar; Sandi Lubis (LPPM Universitas Abdurrab, 2025)
Community awareness plays an important role in the effectiveness of sustainable waste management. According to pro-environmental behavior theory, awareness is the first step that directs individuals to behave in environmentally friendly ways, such as disposing of waste properly and sorting it based on type. The purpose of this study is to assess the level and description of community awareness regarding waste management in Timoreng Panua Village, Panca Rijang Subdistrict, Sidenreng Rappang Regency. This study employed a quantitative approach with data collection techniques including questionnaires, observation, and documentation. The population in this study consists of all household heads residing in Timoreng Panua Village, Panca Rijang Subdistrict, Sidenreng Rappang Regency, who are responsible for managing waste in their respective environments, totaling 700 households, with a sample of 88 households. The results indicate that community awareness in Timoreng Panua Village falls into the “Good” category, with an overall average percentage of 73.52%. Meanwhile, the effectiveness of waste management in Timoreng Panua Village as a whole falls into the “Moderate/Neutral” category, with an average percentage of 60.64%. The results of simple linear regression analysis empirically prove that community awareness has a significant and positive influence on the effectiveness of waste management in Timoreng Panua Village.